Platform Derma dalam Talian (E-Assyakirin) - Azhar, Ahmad Ansar; Abdul Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2021)
Platform Online Charity (E-Assyakirin) is an application that enhance conventional existence system that have been used by Assyakirin mosque at Jalan Kebangsaan Taman Universiti, Skudai, Johor to conduct charity program that involve transection of used items (non- tractional money involved). Donors that want to donate their used items need to bring the item into the person who is in charge of the donation program. The item element and entities will be recorded into a book. The item will be stored in Monsque storage room and displayed its entities in a whiteboard to inform the availability of the item. Person who is interested in acquiring the item needs to come and pick up on a specific day which usually in weekends. This system is less efficient because of usage of storage room that need to be maintain time to time and it will consume cost. Furthermore, the usage of book is irrelevant because chances of incomprehensible writing and losing the book are high. Hence, the development of Online Donation Platform (E-Assyakirin) is developed to improve the flow of the existing system. Functional module that this application has are displayed donor items, requesting items and feedback items. Prototype model have been used as methodology of this application. For the design of the application and the flow of the application, AdobeXD is chosen to design the application. As for the development of the application, Java programming with the connection of Firebase as the database are chosen to build the application. At the end of this project, application Online Donation Platform (E-Assyakirin) can accelerate the rate of matching between the item with people who really indeed of the item as well as reducing cost of maintaining the storage room.